The glaucomas : Volume II - open angle glaucoma and angle closure glaucoma - Sampaolesi, Roberto; Zarate, Jorge (Springer Berlin Heidelberg, 2014)
This second volume in a short series on the glaucomas is devoted to the two main types of the disease, open angle glaucoma and angle closure glaucoma. The contents are based on observations and experience gained during the management of more than 40,000 hospital and 7,000 private patients, with follow-up of 10 to 50 years. The book is comprehensive in scope. All aspects of diagnosis are carefully examined, surgical indications and techniques are explained, and the role of medical treatment is evaluated. Importantly, chapters are included on topics that are frequently overlooked in other books but are important to early diagnosis, such as diurnal pressure curve, HRT, and non-conventional perimetry. This volume provides a wealth of information and includes almost 1000 illustrations, the majority in color, as well as an accompanying DVD of surgical techniques. It will be an invaluable asset for all ophthalmologists.